Sensualitas Perempuan Dalam Iklan Televisi (Analisis Semiotika Roland Barthes Pada Iklan Kispray Versi Gold For Moment) - Larasari Dwi Putri; Dian Novitasari; Darwadi M Suwarno (Universitas Baturaja, 2020)
Advertising turns out not only to function as a promotional medium but also to contain ideologies that are capable of influencing people's mindsets. At present there are many advertisements that use the symbol of a woman as it is known that a woman's body is now defined as having a body that contains sensuality that can cause lust for men. This study aims to analyze ad impressions that contain elements of female sensuality by using the semiotic theory of Roland Barthes, to find a meaning that is hidden behind a sign from the markers and markers contained in the advertisement. This study uses a qualitative approach and in this study uses a type of critical paradigm. The results of this study can be found that there is an element of sensuality in the Kispray advertisement version of the gold for moment starts from excessive image taking on a woman's body and there is a myth in the Kispray advertisement version of the gold for moment that women are able to flirt with a sexy look. Facial expressions, body gestures and female voice tones can provoke male sexual imagination and the fragrance of Kispray gold is equivalent to the perfume of luxury perfume.